Kostmann’s syndrome with chronic pneumonia and lymphocytosis: effect of recombinant human G-CSF - Yetgin, Sevgi; Özbek, Namık; Tuncer, Murat; Göçmen, Ayhan; Özçelik, Uğur (The Turkish Journal of Pediatrics, 1994)
Kostmann’s syndrome is a congenital disorder characterized by impairment of myeloid differentiation in bone marrow with severe absolute neutropenia. A 17-month-old girl was admitted to the hospital with complaints of recurrent skin infections since birth and severe pneumonia of the right lung which had been resistant to antibiotics since the patient was eight months old. Anemia, severe neutropenia and maturational arrest of granulocytes at the myelocyte stage in bone marrow were detected. At the age of 20 months, a right pneumonectomy was performed because of resistant cystic infection. Postoperatively, she was diagnosed with Kostmann’s syndrome. Recombinant human granulocyte-colony-stimulating factor (rhG-CSF) was administered intravenously at a dose of 3 µg / kg / day, gradually increasing to 60 µg / kg / day in sequential seven-day courses to obtain a neutrophil count of more than 500 cells / mm³. Absolute neutrophil counts increased to greater than 1000 cells / mm³ at a dose of 60 µg / kg / day, and at that time bone marrow aspiration revealed an increase in neutrophilic granulocytic precursors beyond the myelocyte stage. In order to maintain the neutrophil response, a dose of 20 µg / kg / day rhG-CSF subcutaneously was continued successfully. The patient has tolerated rhG-CSF treatment without complications, and infectious attacks have significantly decreased.